To Improve of The Children’s Natural Intelligence with Nature Based Learning - Nori Nopita Sari; Chusnul Muali; Fathor Rozi; Yulis Ernawati; Shofiyatul M (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This research aims to find out about improve of the children's natural intelligence with nature-based learning. This research was conducted at the Institute of Learning Group Mutiara Jati Kraksaan Probolinggo using qualitative research methods with case study type. The sample in the study was principal, teacher A and teacher B. The result of this research, then first  learning design. Learning devices are arranged to fit the purpose of learning. Then the formation of the child's natural intelligence. Nature-based learning is carried out in accordance with the plan that has been prepared with nature arranged interesting activities outside the classroom. The last, factors that affect a child's natural intelligence. Among other factors from the school environment, family environment and community environment